Groups In Context: A New Perspective on Group DynamicsGroups In Context: A New Perspective on Group Dynamics edited by GilletteJonathon and McCollomMarion. Reading, MA: Addison-Wesley, 1990, 365 pp. - Eisenstat, Russell A. (Academy of Management Review, 1992)
This article presents a review of the book ?Groups In Context: A New Perspective on Group Dynamics,? edited by Jonathan Gillette and Marion McCollom.